Music and how it works : the complete guide for kids - Morland, Charlie; Humphries, David (New York, N.Y. : DK/Penguin Random House, 2020)
"Discover how music is made, the many different forms it takes, and the ... artists that make it"--Back cover.
Includes index.
5.7
3-6.
3-6
Keywords: Music appreciation -- Juvenile literature; Music -- Acoustics and physics -- Juvenile literature; Music appreciation; Music -- Acoustics and physics; Music appreciation; Music -- Acoustics and physics